Flipped learning for novices and advanced yarn-crafters in higher education - Härkki Tellervo; Koskela Teija; Kouhia Anna; Rönkkö Marja-Leena (Aberdeen College of Education, 2025)
This research examines student craft teachers' learning in the context of two yarn-craft courses utilising flipped learning to provide inclusive and encouraging learning experiences for all students, despite their significantly differing skill levels. A similar challenge of identifying and implementing pedagogical approaches that account for students' differing entry-level skills exists for several higher education programmes, especially in domains with indirect continuation of compulsory high school courses. Experiencing courses as too easy or too demanding has a negative impact on student achievement. Therefore, this research asks how students participating in these courses described their learning and whether novices and advanced yarn-crafters were content with the flipped-learning implementations. From the two yarn-technique flipped-learning courses, 51 student craft teachers participated in this study. Students were instructed to set their own learning goals and conduct self-assessments. All student-provided materials were collected as research data and analysed using thematical qualitative analyses. The results show that the possibility of tailoring their learning directed students' learning in personally meaningful directions. However, the need for teacher support was not determined by yarn- craft skills alone, but also by students' regulation of their own learning. For teachers, flipped learning provides an impressive window into students' diverse learning needs.